PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP MOTIVASI DAN BERFIKIR KRITIS SISWA - Yosep Heristyo Endro Baruno; Juliana Loes; Yosua Padama; Hafsah Sri Indah Rezeki Siregar (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
This research aims to identify and analyze the influence of contextual learning on students’ learning motivation and their ability to think critically. This study carries out a meta-analysis of a number of empirical studies that have been conducted in the context of contextual learning. The results of the analysis show that contextual learning has a significant influence on students’ learning motivation and their ability to think critically. These findings indicate the importance of integrating real-world contexts in the learning process to increase students’ motivation and their ability to analyze information critically. The practical implication of these findings is the need to develop learning strategies that emphasize the application of real contexts in teaching to increase student engagement and achievement in learning.